Предмет: Алгебра, автор: kirillh95

Кто нибудь, решите уравнение!!!2 примера:
1. (2x-3)^2+(3-4x)(x+5)=82
2. (x-1)(x+1)=2(x-5)^2-x(x-3)


kirillh95: Пожалуйста, решите 2 уравнения!

Ответы

Автор ответа: snow99
2
1)
 {(2x - 3)}^{2}  + (3 - 4x)(x + 5) = 82 \\ 4 {x}^{2}  - 12x + 9 + 3x - 4 {x}^{2}  + 15 - 20x = 82 \\  - 29x = 58 \\ x =  - 2
Ответ: -2.

2)
(x - 1)(x + 1) = 2 {(x - 5)}^{2}  - x(x - 3) \\  {x}^{2}  - 1 = 2 {x}^{2}  - 20x + 50 -  {x}^{2}  + 3x \\  {x }^{2}  - 1 =  {x}^{2}  - 17x + 50 \\  {x}^{2}  -  {x}^{2}  + 17x = 50 + 1 \\ 17x = 51 \\ x = 3
Ответ: 3
Похожие вопросы